CGIAR Research Program on Forests, Trees and Agroforestry - Plan of Work and Budget 2019 - CGIAR Research Program on Forests, Trees and Agroforestry (CGIAR Research Program on Forests, Trees and Agroforestry, 2019)
FTA work planning is based on a priority setting process, aiming at focusing research towards major development demands and knowledge gaps, orienting FTA towards the implementation of the SDGs and other global commitments. The 22 operational priorities of FTA, as elaborated for the 2018 POWB (see list in Annex 1) build on the comparative advantages of FTA and its partners in order to maximize effectiveness and impact.